A Study on the Relationship Between Breastfeeding Type and Urinary Tract Infections in Children Under the Age of Two Years (Texas Journal of Medical Science, 2023)
This study aimed to investigate the relationship between breastfeeding practices and urinary tract infections (UTIs) in children under the age of two years. Data were obtained from Al-Rifai, Souq AlShuyukh, and Bint Al-Huda maternity hospitals, as well as private laboratories affiliated with outpatient clinics